2015
DOI: 10.1016/j.gaitpost.2014.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on the variability and stability of gait: A cross-sectional treadmill study in healthy individuals between 20 and 69 years of age

Abstract: Falls during walking are a major health issue in the elderly population. Older individuals are usually more cautious, walk more slowly, take shorter steps, and exhibit increased step-to-step variability. They often have impaired dynamic balance, which explains their increased falling risk. Those locomotor characteristics might be the result of the neurological/musculoskeletal degenerative processes typical of advanced age or of a decline that began earlier in life. In order to help determine between the two po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
104
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(116 citation statements)
references
References 30 publications
9
104
1
2
Order By: Relevance
“…An increasing interest in lateral control is emerging, given that impairments in this domain are thought to increase falls risk [19, 20]. Recent findings in nonlinear gait analysis even suggest that gait stability in the frontal plane is of interest for predicting fall risk [21, 22]. Finally, lateral and postero-lateral falls have greater hip injury potential, including hip fractures, than falls in other directions [2325].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing interest in lateral control is emerging, given that impairments in this domain are thought to increase falls risk [19, 20]. Recent findings in nonlinear gait analysis even suggest that gait stability in the frontal plane is of interest for predicting fall risk [21, 22]. Finally, lateral and postero-lateral falls have greater hip injury potential, including hip fractures, than falls in other directions [2325].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to healthy controls, PwMS display greater variability in step width and single support time based on coefficient variation (Sosnoff et al, 2012). Linear measures of variability such as coefficient of variation or standard deviation provide information about the magnitude of variability within a time series (O’Connor et al, 2012; Terrier and Reynard, 2015). Nonlinear variability measures provide information on the temporal structure of variability within a time series (Harbourne and Stergiou, 2009; Stergiou and Decker, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is thus surmised that more trials spread over more than 1 day can significantly improve the reliability of the measurement. To present, studies employing the Lyapunov analysis for examining the stability of gait have focused on differences between groups of young and older age (Buzzi et al, 2003; Kang and Dingwell, 2008; Hamacher et al, 2011, 2015; Terrier and Reynard, 2015; Mehdizadeh, 2017) or health and pathology (Moraiti et al, 2007, 2010; Lamoth et al, 2010; Look et al, 2013; Wurdeman et al, 2013; Kao et al, 2014; Hoogkamer et al, 2015). However, interventional or prospective study designs examining the resulting MLE might require higher degrees of accuracy and thus more than one measurement trial and day.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in walking conditions reported good intrasession reliability (Kang and Dingwell, 2006b; van Schooten et al, 2013; Reynard and Terrier, 2014; Reynard et al, 2014; Rábago et al, 2015). Based on this, it was argued that differences between young and older adults (Buzzi et al, 2003; Kang and Dingwell, 2008; Terrier and Reynard, 2015; Mehdizadeh, 2017) as well as patients with moderate neurological gait disorders (Reynard et al, 2014) where instability is expected, can be discovered with the MLE. However, the reliability of the MLE is decreased between days (van Schooten et al, 2013; Reynard and Terrier, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation